Improvement of Hyperglycemia and Sexual Dysfunction in Diabetic Female Rats by an Artificial Endocrine Pancreas Developed from Mouse β Cells - TERADA, Misao; SAITO, Toru R.; KROMKHUN, Pudcharaporn; FUNGFUAUG, Wirasak; HASHIMOTO, Haruo; YOKOSUKA, Makoto; MORITANI, Naoki; NAKADA, Tomoaki (Experimental Animals, 2010)
We investigated the effects of a bioartificial endocrine pancreas (Bio-AEP) produced by mouse β cells on sexual dysfunction of streptozotocin (STZ)-induced diabetic female rats. Female rats were administered STZ (60 mg/kg BW, i.v.) at the age of 10 weeks and transplanted with a Bio-AEP including mouse β cells at the age of 14 weeks (STZ+Bio-AEP group). Lordosis and proceptive sexual behavior of female rats were observed. The results showed that after the Bio-AEP transplant blood glucose recovered from 380–450 mg/dl induced by streptozotocin to 140–230 mg/dl and suppressed lordosis and proceptive behavior also recovered. These results suggest that it is possible to reverse sexual dysfunction by continuous administration of mouse insulin.